The Effect of Social Media Influencer on Brand Switching Behavior of Millennial and Generation Z - Singh, Sirjana; Bajracharya, Shrija; Rijal, Samragyee; Shrestha, Srista; Singh, Shivanth (New Perspective: Journal of Business and Economics, 2024)
This study examines the effect of social media influencers on brand switching behaviors among Millennials and Generation Z in urban areas of Nepal, specifically focusing on the major cities of Kathmandu and Lalitpur. A sample size of 150 respondents was determined using the rule of 1:10. Data were analyzed using regression analysis to assess the relationships between social media influencers and brand switching. The findings indicate that social media influencers play a significant role in influencing customer decisions regarding brand switching. In contrast, opinion leaders and celebrities did not show any significant influence on this behavior. This suggests that social network users, particularly younger consumers, have a substantial impact on brand switching behaviors. The study also highlights the prevalent use of social media among younger demographics, particularly on platforms like Instagram, reinforcing the importance of social media in shaping consumer choices and opinions. The results have important implications for businesses operating in the digital age. By effectively leveraging social media influencers, companies can better tap into the preferences and motivations of Millennials and Generation Z, ultimately fostering brand loyalty and trust. Overall, this research contributes to the understanding of the dynamics between social media influencers and consumer behavior, emphasizing the need for businesses to adapt their marketing strategies to engage effectively with younger consumers in an increasingly digital marketplace.